Projection of Electrical Energy Needs in Bali Using Econometric Methods - Prastika, Komang Cau; Setiawan, I Nyoman; Sukerayasa, I wayan; Giriantari, Ida Ayu Dwi; Ariastina, Wayan Gede; Santiari, Dewa Ayu Sri; Kumara, I Nyoman Satya (Journal of Electrical, Electronics and Informatics; Vol 8 No 2 (2024): JEEI (December 2024), 2025)
Bali is one of the provinces in Indonesia with a densely populated area because it is recognized as the best and most beautiful tourist destination island. This makes the demand for the availability of electrical energy in Bali will increase every year. To solve this problem, forecasting the need for electrical energy in Bali was carried out in 3 scenario modeling. In modeling this scenario, an econometric method is used to project electrical energy needs in Bali in 2024 –2045. The results of this study indicate that the optimistic scenario undergoes an average growth in electricity needs of 8.99% per year with a per capita energy projection of 87,10.13 kWh/capita in 2045. In a moderate scenario, the average growth in electrical energy consumption needs is 6.98% per year with an energy projection per capita is 5,623.91 kWh/capita in 2045. In a pessimistic scenario, the average growth in electrical energy consumption needs is 5.44% per year with an energy projection per capita is 3,913.77 kWh/capita in 2045. Thus, optimistic scenario modeling has the highest growth in electrical energy consumption compared to other scenario modeling.